Investing in a random start American option under competition - Pereira, Paulo J. (2019)
In this paper we develop a model to determine the value of the opportunity to invest in a random start American real option. In contrast to a typical American option, the random start option only exists if an exogenous event occurs materializing the American option to invest. In addition, the effect of competition is also considered in the model. A higher risk of competition and a higher probability of the exogenous event promotes investment. Uncertainty has a non-monotonic effect on investment timing.